Environment-Aware Regression for Indoor Localization based on WiFi Fingerprinting - Mendoza-Silva, German (2022)
Mendoza-Silva, G., Costa, A. C., Torres-Sospedra, J., Painho, M., & Huerta, J. (2022). Environment-Aware Regression for Indoor Localization based on WiFi Fingerprinting. IEEE Sensors Journal, 22(6), 4978 - 4988. https://doi.org/10.1109/JSEN.2021.3073878